Incentivizing collaborative BIM-enabled projects : a synthesis of agency and behavioral approaches - Chang, Chen-Yu, 1969- (Project Management Institute, Inc., 2018)
"The use of digital representations to aid in projects--Building Information Modeling (BIM)--is gaining traction worldwide as an effective and beneficial approach to executing projects that can reduce errors and improve project results. These crucial benefits are prompting many businesses and governments to mandate its use, while others search for ways to grow and incentivize the practice. In Incentivizing Collaborative BIM-Enabled Projects: A Synthesis of Agency and Behavioral Approaches, Chen-Yu Chang, PhD, explains the current state of BIM use in three distinct countries: China, the United Kingdom, and the United States. Following multiple case studies in each country, Professor Chang explores the explicit and implicit motivators that may drive BIM participation and the factors that can influence its effectiveness. The case studies offer multiple perspectives on why and how BIM-enabled projects are adopted and provide a lens for understanding BIM at varying levels of maturity and in different environments. Understanding the motivators behind the current state of BIM-enabled projects facilitates the design of incentive structures for future BIM projects. As BIM continues to evolve and transform the industry, this research provides valuable insight into the best practices for incentivizing its use. This theoretical approach gives researchers and organizations new tools and ideas to help build their own strategies to encourage BIM use and better understand its place in managing projects"--